2011
DOI: 10.4236/aces.2011.13020
|View full text |Cite
|
Sign up to set email alerts
|

Development of Siliconized Epoxy Resins and Their Application as Anticorrosive Coatings

Abstract: The present work involves the development of siliconized epoxy resin to overcome the drawback of epoxy resin like poor impact strength, high rigidity and moisture absorbing nature because of which they are not applied as corrosion resistant coating. By embedding silicone into the back bone of polymeric resin the above drawback can be reduced to substantial level. For achieving this, siliconised epoxy resins were prepared by reacting amine terminated silicone resin with novolac epoxy resin and meta-phenylenedia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(8 citation statements)
references
References 12 publications
(12 reference statements)
0
8
0
Order By: Relevance
“…16 Many siliconized epoxy hybrid materials were prepared using the above methodology and reported in literature. [17][18][19][20] However, reports on similar materials having urethane moieties are very rare. 21 The production of such novel hybrid sol-gel materials of superior mechanical and barrier properties is still a very challenging area for research.…”
Section: Introductionmentioning
confidence: 99%
“…16 Many siliconized epoxy hybrid materials were prepared using the above methodology and reported in literature. [17][18][19][20] However, reports on similar materials having urethane moieties are very rare. 21 The production of such novel hybrid sol-gel materials of superior mechanical and barrier properties is still a very challenging area for research.…”
Section: Introductionmentioning
confidence: 99%
“…5). It is harder than silica‐containing epoxy coatings [8] and is therefore more scratch‐resistant and easier to use. It was confirmed that the hardness is applicable as a spacer.…”
Section: Characteristics Of Coating Materials With Nonlinear‐resistan...mentioning
confidence: 99%
“…However, due to its high rigidity, low shock resistance, and hygroscopic properties, the use of epoxy resin as an anticorrosion coating has become questionable. The disadvantages can be compensated by using composites of different materials [ 15 ].…”
Section: Introductionmentioning
confidence: 99%